1988
DOI: 10.1093/oxfordjournals.humrep.a136808
|View full text |Cite
|
Sign up to set email alerts
|

Chorionic gonadotrophin-β mRNA, a trophoblast marker, is expressed in human 8-cell embryos derived from tripronucleate zygotes

Abstract: Human chorionic gonadotrophin beta (HCG-beta) is a trophoblast marker. Its expression is normally limited to syncytiotrophoblast cells of chorionic villi, although it is known to be secreted from the human embryo as early as 7 days post-fertilization. To examine the onset of embryonic transcriptional activity of the gene encoding this polypeptide we have performed in-situ hybridization to cellular RNAs of human tripronucleate preimplantation embryos. We see expression of HCG-beta RNA at the 6-8-cell stage, bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(70 citation statements)
references
References 9 publications
3
64
0
3
Order By: Relevance
“…hCG was shown having direct paracrine effects on the endometrium that precede its endocrine role of rescuing the corpus luteum, and regulates IGFBP-1 and prolactin in decidualized human endometrial stromal cells [51][52][53][54]. Here, hCG did not affect MFGE8 gene expression levels, consistent with previous results from our laboratory showing no change in primary human endometrial epithelial cells [31].…”
Section: Discussionsupporting
confidence: 91%
“…hCG was shown having direct paracrine effects on the endometrium that precede its endocrine role of rescuing the corpus luteum, and regulates IGFBP-1 and prolactin in decidualized human endometrial stromal cells [51][52][53][54]. Here, hCG did not affect MFGE8 gene expression levels, consistent with previous results from our laboratory showing no change in primary human endometrial epithelial cells [31].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, ␤-hCG7 encodes a protein differing in three amino acids and is expressed at low levels in normal nonmalignant tissues (20,22,23). During pregnancy hCG is initially produced by the blastocyst 6 -8 days after fertilization (24,25) and later by the syncytiotrophoblast (26). The level of hCG increases during the first trimester of pregnancy and decreases to 10% of the peak value during the second and third trimesters (27).…”
Section: Cd25mentioning
confidence: 99%
“…The hCG-subunits are already transcribed in 8-cell embryos (Bonduelle et al 1988) and the blastocyst has been shown to secrete relatively high concentrations of bioactive hormone (Lopata and Hay 1989). Since hCG is produced by syncytiotrophoblasts after the fusion of cytotrophoblasts as a function of trophoblast differentiation (Hoshina et al 1985), and several endometrial cytokines considered essential for implantation, such as LIF (Sawai et al 1995) andM-CSF (Garcia-Lloret et al 1994) have been shown to modulate hCG-biosynthesisprobably by interfering with trophoblast differentiation -hCG could well be a key regulator, triggering whether or not the embryo will implant.…”
Section: The Role Of Hcgmentioning
confidence: 99%